An age-downregulated ribosomal RpS28 protein variant regulates the muscle proteome. Issue 7 (11th May 2021) - Jiao, Jianqin; Kavdia, Kanisha; Pagala, Vishwajeeth; Palmer, Lance; Finkelstein, David; Fan, Yiping; Peng, Junmin; Demontis, Fabio
Abstract: Recent evidence indicates that the composition of the ribosome is heterogeneous and that multiple types of specialized ribosomes regulate the synthesis of specific protein subsets. In Drosophila, we find that expression of the ribosomal RpS28 protein variants RpS28a and RpS28-like preferentially occurs in the germline, a tissue resistant to aging and that it significantly declines in skeletal muscle during aging. Muscle-specific overexpression of RpS28a at levels similar to those seen in the germline decreases early mortality and promotes the synthesis of a subset of proteins with known anti-aging roles, some of which have preferential expression in the germline. These findings indicate a contribution of specialized ribosomal proteins to the regulation of the muscle proteome during aging.